Mineralogy and provenance of the TiO₂ - ilmenite heavy mineral sand deposit of Nataka - Elias, Sílvio José (Department of Geological Sciences, 2017)
The Nataka heavy mineral sand deposit occurs along the northeast Mozambique coastline. It comprises a regional Pleistocene elliptical structure extending from Somalia, passing through Kenya, Tanzania, Madagascar and Mozambique, to Richards Bay in South Africa. The deposit consists of fine- to medium- grained, unconsolidated red sediments, hosting heavy minerals. The deposit mineral assemblage is made up of non-valuable phases comprising mostly magnetite, hematite, chromite, monazite, and the valuable phases dominated by ilmenite (50.91 wt. %), with additional zircon and rutile (9.96 and 3.52 wt. % respectively). The total heavy minerals comprise about 5% volume, of which 2 % are valuable heavy minerals making up about 445 Mt (million tonnes) probable resources. This study focuses on the mineralogical characterization of ilmenite from the Nataka deposit, alongside with sediment provenance. Mineralogical and chemical characterisation of ilmenite undertaken on 32 samples from 16 selected drill holes using a combination of QEMSCAN and EPMA revealed that the ilmenite has undergone different stages of alteration, at distinct environment conditions, yielding products spanning from hydrated ilmenite to leucoxene. The alteration dominantly involved groundwater, which was oxidizing and acidic, hence the predominance of ilmenite-pseudorutile alteration. Long exposure to direct sunshine has been hypothesized as a different process that might have favoured the direct alteration of ilmenite to leucoxene and of pseudorutile to leucoxene, on a smaller scale. The major impurities in the ilmenite are Al and Si, which are enriched in the advanced ilmenite alteration products (leucoxene), where they fill pores and cracks. Chromium impurities occur as discrete grains of chrome spinel. The compositional variety of magnetite, Cr-spinel, tourmaline, zircon and rutile indicate major contribution from granitoid terranes, subjected to granulite metamorphic facies (750 to 1000 :C), and minor contribution from mafic plutonic intrusions. The granitoid field as a sediment source area if analysed in conjunction with zircon ages (1100 – 900 Ma, 900 – 700 Ma, and 650 – 500 Ma), and zircon δ¹⁸O (7.07 ‰) is consistent with preferential sourcing from the proximal Mesoproterozoic Nampula Complex, with some contribution from igneous plutonic rocks from Xixano, Lalamo and Montepuez Complexes.